Pathological spectrum of bile duct lesions from chronic bile duct injury to invasive cholangiocarcinoma corresponding to bile duct imaging findings of occupational cholangiocarcinoma. (30th December 2015) - Kinoshita, Masahiko; Kubo, Shoji; Nakanuma, Yasuni; Sato, Yasunori; Takemura, Shigekazu; Tanaka, Shogo; Hamano, Genya; Ito, Tokuji; Terajima, Hiroaki; Yamada, Terumasa; Nakamori, Shoji; Arimoto, Akira; et al.
Abstract: Background: We aimed to identify the pathological characteristics of occupational cholangiocarcinoma. Methods: We examined the location and distribution of the carcinomas: atypical epithelium including biliary intraepithelial neoplasia (BilIN) and intraductal papillary neoplasm of the bile duct (IPNB); and chronic bile duct injuries in operative or autopsy liver specimens from 16 patients. We examined the detailed pathological findings and diagnostic imaging of three patients. Immunohistochemical analysis using primary antibodies against γH2AX and S100P was performed. Results: BilIN and chronic bile duct injury were observed in 16 patients, and IPNB or invasive IPNB was observed in 11 patients. BilIN, IPNB, and/or chronic bile duct injury were observed in almost all the large bile ducts. Regional dilatation of the bile ducts without tumor‐induced obstruction revealed such pathological changes. Highly positive results for the γH2AX and S100P markers were noted in invasive carcinoma, BilIN, and IPNB, whereas positive results for γH2AX and negative results for S100P were noted in non‐neoplastic biliary epithelium. Conclusions: The carcinogenic process of occupational cholangiocarcinoma comprised chronic bile duct injury and DNA damage in almost all the large bile ducts, along with induction of precancerous lesions and development of invasive carcinoma. Such pathological findings reflected radiological changes on diagnostic imaging. Abstract : Highlight In patients with occupational cholangiocarcinoma, Kinoshita and colleagues report a carcinogenic process consisting of chronic bile duct injury with DNA damage that occured within almost all of the large bile ducts, the induction of pre‐ or early cancerous lesions such as BilIN and IPNB, and the development of invasive carcinoma.